Preparation of nano‐pico droplets using an open fibrous system. Issue 1 (11th November 2022) - Xu, Bojie; Chen, Xuan; Zhao, He; Zhang, Zhen; Liu, Huan
Abstract: Manipulation and dispensing of ultra‐tiny droplets have attracted extensive research attention for their applications. Current approaches for dispensing liquids normally involve the use of micronozzles and microtips, which, however, suffer from limitations of clogging, high cost, and fragility. Here, we developed a facile open fibrous system for preparing nano‐pico droplets in a facile way, where the macroscopic droplet on a micro‐/nano‐textured copper fiber could be dispersed to a number of tiny droplets by applying and removing a suitable electric potential. The on‐site tunable interfacial energy, imparted by the electrical alterable density and orientation of the water molecules on the interface, leads to fine control of the spreading and retraction of the liquid on a large scale. Meanwhile, the fibrous microporous structure promotes the splitting of the liquid film based on the domain‐limiting effect during the retracting process. As a synergistic consequence, a big droplet firstly spreads completely on the poised fiber into a thin liquid film, which was then split and retracted toward the numerous anchoring points on the textured surface by removing the potential. Consequently, a big droplet can be dispersed into numerous nano‐pico droplets in a controllable way. The strategy is applicable for versatile low‐surface‐energy liquids, offering an innovative open system for continuous preparation of nano‐pico droplets. Abstract : Using an open fibrous system, we develop a facile electrochemical strategy for preparing nano‐pico droplets in a facile way, where the macroscopic droplet on a micro‐/nano‐textured copper fiber could be dispersed to a number of tiny droplets by applying and removing a suitable electric potential. The strategy is applicable for versatile low‐surface‐energy liquids, offering an innovative open system for continuous preparation of nano‐pico droplets.